2016
DOI: 10.18632/oncotarget.13024
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed miRNAs in triple negative breast cancer between African-American and non-Hispanic white women

Abstract: Triple Negative Breast Cancer (TNBC), a clinically aggressive subtype of breast cancer, disproportionately affects African American (AA) women when compared to non-Hispanic Whites (NHW). MiRNAs(miRNAs) play a critical role in these tumors, through the regulation of cancer driver genes. In this study, our goal was to characterize and compare the patterns of miRNA expression in TNBC of AA (n = 27) and NHW women (n = 30). A total of 256 miRNAs were differentially expressed between these groups, and distinct from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
61
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(87 citation statements)
references
References 76 publications
12
61
1
Order By: Relevance
“…This 20patient subset included 6 TNBC patients and 14 NTN patients. Principal component analysis (PCA) of 3000 AIMs overlaid with self-reported ethnicity of our cases showed separation of distinct ancestral populations [22] when merged with two populations from the 1000 Genomes Project: African descent (AFR) and ad mixed American (AMR) (Fig. 3c).…”
Section: Esrrb Does Not Have Copy Number Loss In Tnbcmentioning
confidence: 89%
See 1 more Smart Citation
“…This 20patient subset included 6 TNBC patients and 14 NTN patients. Principal component analysis (PCA) of 3000 AIMs overlaid with self-reported ethnicity of our cases showed separation of distinct ancestral populations [22] when merged with two populations from the 1000 Genomes Project: African descent (AFR) and ad mixed American (AMR) (Fig. 3c).…”
Section: Esrrb Does Not Have Copy Number Loss In Tnbcmentioning
confidence: 89%
“…Next, we sought to determine if the observed decrease in ESRRB mRNA expression found in TNBC/BLBC may be due to copy number loss. We approached this by analyzing an independent, 106-patient cohort of Caucasian (CW) and African American (AA) patients with TNBC and non TNBC (NTN) using array comparative genomic hybridization (aCGH) as previously described by Sugita, et al [22]. ESRRB copy number was calculated and defined as deletion, loss, gain, or amplification, and demographic information was analyzed for associations with ESRRB copy number changes ( Fig.…”
Section: Esrrb Does Not Have Copy Number Loss In Tnbcmentioning
confidence: 99%
“…A genome-wide analysis of CNAs conducted in different types of cancer revealed that a specific tumor type presents 17% of regions with amplifications and 16% of deletions, compared with <0.5% in normal samples (40). The patterns of these somatic tumor alterations, as CNVs, may also vary within ethnic groups (35,41). The majority of the studies assessing these alterations, in addition to their gene and epigenetic expression profiles, are in White European and African American patients with breast cancer (35,(40)(41)(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…The patterns of these somatic tumor alterations, as CNVs, may also vary within ethnic groups (35,41). The majority of the studies assessing these alterations, in addition to their gene and epigenetic expression profiles, are in White European and African American patients with breast cancer (35,(40)(41)(42)(43)(44)(45). Few studies have been performed in patients from Sub-Saharan countries (24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation